-9n-8(2+2n)=-28

Simple and best practice solution for -9n-8(2+2n)=-28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9n-8(2+2n)=-28 equation:


Simplifying
-9n + -8(2 + 2n) = -28
-9n + (2 * -8 + 2n * -8) = -28
-9n + (-16 + -16n) = -28

Reorder the terms:
-16 + -9n + -16n = -28

Combine like terms: -9n + -16n = -25n
-16 + -25n = -28

Solving
-16 + -25n = -28

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + -25n = -28 + 16

Combine like terms: -16 + 16 = 0
0 + -25n = -28 + 16
-25n = -28 + 16

Combine like terms: -28 + 16 = -12
-25n = -12

Divide each side by '-25'.
n = 0.48

Simplifying
n = 0.48

See similar equations:

| 35000+250p=17615+550p | | 5a^2+2b^2=10cforb | | 3-6x+6x+12=12x-24 | | (-4)+x=(-7) | | .83v+10=5 | | (-8-3)3-(4-6-2)= | | 17615+550p=74815 | | 3x-25=2x+2 | | -8x+4(x+2x-8)=-12 | | 0.4(x-3.5)=5.8x+1.84 | | 5/2a-5=30 | | 3x^8+30x^7+48x^6=0 | | (5-11i)-(-7+5i)= | | 75*60=95*40x | | .5w+5=13 | | (-3)=(-5)-x | | 2x-2[8(x+4)-(x-4)]-2= | | 8h-13-h=4-27h-2 | | 7-12x-5-2x=4 | | 93.96=4.7*p+8.7*p-2.6*p | | (-3)(14)(1.8)= | | 17615+550p=0 | | -42x^2-57x+120=0 | | 6-8(n-5)=6(-8n+2)-6 | | .75k+9=6 | | 11=[m+7] | | (81)^3/4 | | (-4)-x=6 | | (81)^(-3/4) | | 93.96=4.7*p+8.7*p-.6*p | | 3x+6-2x+8=24 | | 4/s–3=-2/5 |

Equations solver categories